2008
DOI: 10.1016/j.copbio.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Sloppiness, robustness, and evolvability in systems biology

Abstract: The functioning of many biochemical networks is often robust-remarkably stable under changes in external conditions and internal reaction parameters. Much recent work on robustness and evolvability has focused on the structure of neutral spaces, in which system behavior remains invariant to mutations. Recently we have shown that the collective behavior of multiparameter models is most often sloppy: insensitive to changes except along a few 'stiff' combinations of parameters, with an enormous sloppy neutral sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 45 publications
5
166
0
1
Order By: Relevance
“…As well as the values of individual parameters, we may also be interested in the dependencies between parameters. In particular, the related concepts of sloppiness and identifiability in biological models have recently received much attention-in the context of possible biological significance and for optimal experimental design (12,(36)(37)(38)(39). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As well as the values of individual parameters, we may also be interested in the dependencies between parameters. In particular, the related concepts of sloppiness and identifiability in biological models have recently received much attention-in the context of possible biological significance and for optimal experimental design (12,(36)(37)(38)(39). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While deletions of individual nodes of a system affect the system to a small degree, elimination of hubs causes major disruption as this leaves small isolated node clusters uninteracting (Albert et al 2000). Not only topology but also gene duplication can play an important part in robustness (Daniels et al 2008). To understand network robustness requires investigation into the functional and dynamic changes that a perturbation causes , thereby viewing robustness as the systems property that it is seen to be (Barkai and Leibler 1997).…”
Section: Robustnessmentioning
confidence: 99%
“…Many different mathematical approaches have been used to compare robustness of systems (Daniels et al 2008;Grimbs et al 2007). Westerhoff showed that the higher the robustness of a variable towards changes in enzyme activities, the lower the fragility and the lower the corresponding concentration control coefficient (Westerhoff 2007).…”
Section: Robustnessmentioning
confidence: 99%
“…It has been noted many times that ODE models of biochemical networks generally exhibit widely varying parameter sensitivities [24][25][26][27][28]; investigation of second-order sensitivities of these models, evaluated at the maximum likelihood, often reveals a wide eigenvalue spectrum that itself may change depending on the point in parameter space at which it is calculated. In settings with such varying parameter scalings, standard Markov chain Monte Carlo (MCMC) samplers generally have very poor mixing properties and produce highly correlated samples [23], resulting in estimates of the required Bayesian quantities with large Monte Carlo errors.…”
Section: Introductionmentioning
confidence: 99%